Liver metastases are less established after gasless laparoscopy than after carbon dioxide pneumoperitoneum and laparotomy in a mouse model - Ishida, H; Hashimoto, D; Takeuchi, I; Yokoyama, M; Okita, T; Hoshino, T (Surgical endoscopy, 2002)
Although the liver is the most frequent site of cancer recurrence after conventional open surgery for colorectal cancer, the effect of laparoscopic procedures with or without gas insufflation on the development of liver metastases is largely unknown. Male BALB/C mice inoculated intraportally with colon 26 cells were randomized to undergo carbon dioxide pneumoperitoneum (n = 14), abdominal wall lifting (n = 14), or full laparotomy (n = 12), or to serve as control subjects without any procedures other than tumor inoculation (n = 13). The growth of liver metastases 14 days after surgery was enhanced after full laparotomy (p < 0.01) and pneumoperitoneum (p = 0.02), as compared with that in the control subjects, whereas there was no difference in the growth of liver metastases between abdominal wall lifting and the control condition (p = 0.99). These results suggest that the defense against liver metastasis is better preserved after the gasless procedure than after laparotomy and carbon dioxide pneumoperitoneum in the reported animal model.